A Juridical Analysis of Law Number 8 of 2016 on Persons with Disabilities: Fulfilling the Principle of Accessibility to Enhance Legal Literacy - Yenti Kristina Dewi; Poltak Siringo-ringo; Marudut Silitonga (International Journal of Science and Environment (IJSE), 2026)
The purpose of this thesis research is to examine the regulation of legal protection for persons with disabilities under the prevailing positive law in Indonesia. In addition, it aims to analyze the responsibility of the state in fulfilling accessibility for persons with disabilities. The problems addressed in this study are: (1) How is the regulation of legal protection for persons with disabilities under positive law? (2) How is the state’s responsibility in fulfilling accessibility for persons with disabilities? The research method employed is normative legal research, using statutory and conceptual approaches. The findings show that legal protection and the fulfillment of accessibility rights for persons with disabilities require adequate facilities, infrastructure, and more integrated and sustainable efforts. Furthermore, synergy among policymakers plays an important role in strengthening legal protection for persons with disabilities. The state’s responsibility in ensuring accessibility rights for persons with disabilities is manifested in equal opportunities, independence, full participation, and dignity. These efforts are carried out through the optimization of coordination among relevant authorities, inclusive policymaking, provision of disability-friendly facilities and services, and raising public awareness on disability issues.